Kashmir Pending: Narrative and Ideology in a Graphic Novel - Hogan, Patrick C. (Narrative Works, 2014)
Kashmir Pending (2007) is the graphic novel of a man who joined the militant insurgency against Indian rule in Kashmir, but who eventually became disillusioned with the revolutionaries. It is valuable in portraying some aspects of the situation in Kashmir that are largely absent from mainstream treatments of the conflict. Nonetheless, it is problematic in a number of ways, ranging from its somewhat unrepresentative apportioning of the violence in Kashmir to its use of a childhood model of militants in its emplotment of the insurgency. In consequence, the novel arguably reinforces a liberal colonialist ideology regarding Indian control of Kashmir.